Cytonuclear discordance in the Florida Everglades invasive Burmese python (Python bivittatus) population reveals possible hybridization with the Indian python (P. molurus). Issue 17 (19th August 2018) - Hunter, Margaret E.; Johnson, Nathan A.; Smith, Brian J.; Davis, Michelle C.; Butterfield, John S. S.; Snow, Ray W.; Hart, Kristen M.
Abstract: The invasive Burmese python ( Python bivittatus ) has been reproducing in the Florida Everglades since the 1980s. These giant constrictor snakes have caused a precipitous decline in small mammal populations in southern Florida following escapes or releases from the commercial pet trade. To better understand the invasion pathway and genetic composition of the population, two mitochondrial (mtDNA) loci across 1, 398 base pairs were sequenced on 426 snakes and 22 microsatellites were assessed on 389 snakes. Concatenated mtDNA sequences produced six haplotypes with an average nucleotide and haplotype diversity of π  = 0.002 and h  =   0.097, respectively. Samples collected in Florida from morphologically identified P. bivittatus snakes were similar to published cytochrome oxidase 1 and cytochrome b sequences from both P. bivittatus and Python molurus and were highly divergent (genetic distances of 5.4% and 4.3%, respectively). The average number of microsatellite alleles and expected heterozygosity were N A  = 5.50 and H E  = 0.60, respectively. Nuclear Bayesian assignment tests supported two genetically distinct groups and an admixed group, not geographically differentiated. The effective population size ( N E  = 315.1) was lower than expected for a population this large, but reflected the low genetic diversity overall. The patterns of genetic diversity between mtDNA and microsatellites were disparate, indicating nuclear introgression of separate mtDNA lineages corresponding to cytonuclear discordance. The introgression likely occurred prior to the invasion, but genetic information on the native range and commercial trade is needed for verification. Our finding that the Florida python population is comprised of distinct lineages suggests greater standing variation for adaptation and the potential for broader areas of suitable habitat in the invaded range. Abstract : To better understand the genetic diversity of the invasive Burmese python ( Python bivittatus ) population in Florida, two mitochondrial loci (mtDNA; 1, 398 bps) were sequenced on 426 snakes and 22 microsatellites were genotyped on 389 snakes. Nuclear Bayesian assignment tests supported two genetically distinct groups and an admixed group. Patterns for genetic diversity between mtDNA and microsatellites were disparate, indicating cytonuclear discordance corresponding to past breeding of Python molurus and P. bivittatus species.